The impact of an experimental nutritional intervention in childhood on education among Guatemalan adults - Maluccio, John; Hoddinott, John F.; Behrman, Jere R.; Martorell, Reynaldo; Quisumbing, Agnes R.; Stein, Aryeh D. (International Food Policy Research Institute, 2006)
Early childhood nutrition is thought to have important effects on education, broadly defined to include various forms of learning. We advance beyond previous literature on early childhood nut ition on education in developing countries by (1) using unique longitudinal data from a nutritional experiment with lifetime educational measures; (2) avoiding confounding the estimates by excluding potentially endogenous right-side variables; and (3) using estimators that allow for nonnormal distributions. Our results indicate significantly positive, and fairly substantial, effects of the randomized intervention a quarter century after it ended: increased grade attainment by women, via increased likelihood of entering and completing primary school and some secondary school; speedier grade progression by women; higher scores on cognitive tests for both men and women; and higher scores on educational achievement tests for both men and women. To account for possible biases in the calculation of standard errors and to control for sample attrition, alternative estimations were run and found to be robust.